Assessing the feasibility of impregnating phase change materials in lightweight aggregate for development of thermal energy storage systems - Kheradmand, M. (Elsevier Ltd, 2015)
This paper assesses the feasibility of impregnation/encasement of phase change materials (PCMs) in lightweight aggregates (LWAs). An impregnation process was adopted to carry out the encasement study of two different PCMs in four different LWAs. The leakage of the impregnated/encased PCMs was studied when they were submitted to freeze/thawing and oven drying tests, separately. The results confirmed that, the impregnation/encasement method is effective with respect to the large thermal energy storage density, and can be suitable for applications were PCMs cannot be incorporated directly such as asphalt road pavements. Â© 2015 Elsevier Ltd. All rights reserved.